The Use of E-Faciliatation in Teaching And Learning of Algebra Among Secondary Schools Students in Gwoza Local Government Area of Borno State, Nigeria. (UNIZIK Journal of Educational Management and Policy, 2024)
This study investigated the use of e-faciliatation on Students' achievement in algebra at Gwoza local Government Area of Borno State Nigeria. The study adopted a quasi experimental design type. The study was based on six weeks of continuous interaction with the selected samples drawn from 35 secondary schools. Mathematics Achievement Test (MAT) was developed by the researcher which was duly validated. The reliability index was calculated using Kuder Richardson formula method (K-R 20) which gave 0.78.Two research questions were raised and three research Hypotheses were generated which were tested at 0.05 level of significance using Analysis of Covariance (ANCOVA). Stratified random sampling technique was used in selecting the sample which consists of 105 participants. The experimental group comprises 32 male and 23 female participants. The control group comprises 28 male and 22 female participants. The results of the study revealed that participants who were taught using e-faciliatation performed better significantly than their counterparts taught with the conventional method, and that the female participants taught Using e-faciliatation also achieved better than the male counterparts. It was recommended that e-faciliatation should be infused by the Mathematics teachers when teaching algebra.
Keywords: e-faciliatation, teaching, algebra, secondary school and Student.